2009
DOI: 10.1094/pdis-93-6-0670b
|View full text |Cite
|
Sign up to set email alerts
|

First Report of Cylindrocladium buxicola on Buxus sempervirens in Spain

Abstract: Cylindrocladium buxicola Henricot, included in the EPPO alert list until November 2008, causes a dangerous foliar disease on Buxus spp. that has been recorded in several European countries and New Zealand (3,4). Buxus sempervirens L. (common boxwood) is one of the oldest ornamental garden plants in Europe. In September 2008, we received 10 2- to 3-year-old potted plants of B. sempervirens cv. Suffruticosa from a nursery in Galicia (northwest Spain) where ≈60% of the plants were affected and had finally defolia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
4
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…1). The symptoms we observed were similar to box blight, caused by Cylindrocladium buxicola, reported in Croatia, Spain, Italy, Germany, Belgium and the United Kingdom (Henricot et al, 2000;Brand, 2005;Crepel & Inghelbrecht, 2003;Saracchi et al, 2008;Pintos et al, 2009;Cech et al, 2010).…”
supporting
confidence: 86%
“…1). The symptoms we observed were similar to box blight, caused by Cylindrocladium buxicola, reported in Croatia, Spain, Italy, Germany, Belgium and the United Kingdom (Henricot et al, 2000;Brand, 2005;Crepel & Inghelbrecht, 2003;Saracchi et al, 2008;Pintos et al, 2009;Cech et al, 2010).…”
supporting
confidence: 86%
“…Although the reports of the disease were officially published in 2002, Henricot and Culham (2002) indicated that disease symptoms were first observed in 1994 in the UK. The pathogen has since spread throughout Europe and North America (Akilli et al 2012;Cech et al 2010;Crepel and Inghelbrecht 2003;Elmhirst, Auxier, and Wegener, 2013;Gorgiladze et al 2011;Ivors et al 2012;Saurat et al 2012;Varela et al 2009). Originally confirmed in several states on both coasts of the United States, C. pseudonaviculata has since spread up and down both coasts, as well as most of the eastern United States (Figure 1).…”
Section: Introductionmentioning
confidence: 95%
“…Boxwood blight, caused by Calonectria pseudonaviculata, was reported in England in the mid-1990s and then in New Zealand in 2002. Since the first reports, this disease has spread into European countries such as Austria, Belgium, Croatia, Czech Republic, Denmark, France, Georgia, Germany, Ireland, Italy, the Netherlands, Norway, Slovenia, Spain, Sweden, Switzerland and Turkey (Henricot et al 2000;Brand 2005;Crepel and Inghelbrecht 2003;Saracchi et al 2008;Pintos Varela et al 2009;Cech et al 2010;Gorgiladze et al 2011;Akilli et al 2012). Iran is the only Asian country that has reported this disease.…”
Section: Introductionmentioning
confidence: 99%